PENYELESAIAN SENGKETA NAMA DOMAIN INTERNET TERKAIT HAK MEREK DI INDONESIA - Ni Nyoman Adi Astiti; Samsul Rizal (Jurnal Ilmu Hukum Tambun Bungai, 2018)
This research is an analytical descriptive research that is a research that describes and describes the existing situation or facts about how the implementation of internet domain name registration related to brand rights in Indonesia and how the settlement of internet domain name dispute related to brand rights in Indonesia. The data were analyzed by normative juridical approach, meaning that the data have been compiled systematically and completely and then analyzed qualitatively with the research location in Palangka Raya City and on line. The results of the study concluded the registration of Internet Domain Name in Indonesia using the principle of first-come-first-served service, meaning that who register first then he is entitled to the internet domain name, this is not only regulated in international agreements, but also regulated in Article 23 paragraph (1) of Law No. 11 of 2008 on Information and Electronic Transactions. Internet Domain Name Dispute Resolution Related to Trademark Rights in Indonesia consists of resolving a generic domain name dispute settled with an international arbitration body registered by ICANN. Dissatisfaction with the outcome of the decision of this arbitration body may be submitted to the District Court or Dispute Settlement Body, where the competent jurisdiction is in accordance with paragraph 1 of the Uniform Domain Name Dispute Resolution. The dispute resolution of country internet domain names (ccTLDs) uses the mechanisms set forth in article 75 of Government Regulation No. 82 of 2012 on the Implementation of Electronic Transactions and Systems. Regarding Internet Domain Name Registration in Indonesia, especially generic domains that do not have special requirements in its registration, to strengthen the legality and domain name of the internet to immediately register the domain name as a brand in Indonesia; 2. Dirjen HKI as a place of registration of brands and Registrar and PANDI as the container of domain name registration in order to synergize in drafting a legislation, so it becomes clear the process of registration until the settlement of internet domain name dispute related to brand rights.